Code 8 [videorecording (DVD)] - Chan, Jeff (Screenwriter); Paré, Chris; Amell, Robbie, 1988-; Amell, Stephen, 1981-; Kang, Sung, 1972-; Matchett, Kari; Bryk, Greg, 1972-; Abrams, Aaron, 1978-; Kane, Kyla; Oliveira, Laysla de, 1992-; Alexis, Vlad; Outerbridge, Peter; et al. (Vertical Entertainment, 2020)
In a world where people with exceptional skills are living in poverty, Conner Reed is a strong young man who is laboring to pay for his sick mother's medical treatment. To earn money, he joins a profitable criminal domain led by Garrett, who works for a drug lord.